A quantitative study of the halogenophilic nucleophilic substitution (SN2X) reaction and chalcogenophilic nucleophilic substitution (SN2Ch) reaction - Kuo, Lun-Hsin (2025)
Halogenophilic nucleophilic substitution (SN2X) has a distinctly different reaction pathway compared to the bimolecular nucleophilic substitution reaction (SN2), but they can lead to the same reaction product. However, their differences can be distinguished by studying stereoselective reactions in which both reaction pathways are possible. Herein, we utilize the stereospecific nature of SN2 and the presence of a pro-chiral anion intermediate in SN2X to conduct a quantitative study in which both SN2 and SN2X reactions exist. We developed a procedure supported by kinetic simulations to measure the halogenophilic percentage (X%). We also developed a new parameter, relative halogenophilicity (H), to quantify the intrinsic characteristics of SN2X reactions and found it to correlate well with the Hammett and Mayr postulates. We studied the time dependency of X% under different reaction conditions, which led to the discovery of two new distinct mechanisms: chalcogenophilic nucleophilic substitution (SN2Ch) reaction and bromide-catalyzed dynamic kinetic resolution. The SN2 and SN2X reactions exhibit similar behavior from both thermodynamic and kinetic perspectives, suggesting that they occur to varying degrees in most of the reactions. Consequently, they are inherently linked and should not be considered in isolation.